2016
DOI: 10.1200/jco.2016.66.7527
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Prostate-Specific Antigen Levels in Midlife Predict Lethal Prostate Cancer

Abstract: Purpose Prostate-specific antigen (PSA) level in midlife predicted future prostate cancer (PCa) mortality in an unscreened Swedish population. Our purpose was to determine if a baseline PSA level during midlife predicts lethal PCa in a US population with opportunistic screening. Materials and Methods We conducted a nested case-control study among men age 40 to 59 years who gave blood before random assignment in the Physicians’ Health Study, a randomized, placebo-controlled trial of aspirin and β-carotene among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 28 publications
7
77
0
Order By: Relevance
“…Justification: Although the optimal age for starting PSA screening has not been vigorously studied, our recommendation for starting PSA screening at age 50 comes from the Goteborg trial, which provides randomized data on the benefits of screening in men starting at this age; 11 however, evidence from observational studies suggests that certain men may benefit from PSA screening at an earlier age, with a nearly 5% risk of developing lethal prostate cancer within 15 years for men aged 45-49 with a PSA >4 ng/ml. 38,39 Although it remains unclear which men will benefit from early PSA screening, family history imparts a substantially increased risk of prostate cancer diagnosis at a younger age. Particularly, men aged <50 with a family history of prostate cancer in a first-or second-degree relative have an approximately five-fold and two-fold increased risk of receiving a prostate cancer diagnosis, respectively.…”
Section: Best Screening Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Justification: Although the optimal age for starting PSA screening has not been vigorously studied, our recommendation for starting PSA screening at age 50 comes from the Goteborg trial, which provides randomized data on the benefits of screening in men starting at this age; 11 however, evidence from observational studies suggests that certain men may benefit from PSA screening at an earlier age, with a nearly 5% risk of developing lethal prostate cancer within 15 years for men aged 45-49 with a PSA >4 ng/ml. 38,39 Although it remains unclear which men will benefit from early PSA screening, family history imparts a substantially increased risk of prostate cancer diagnosis at a younger age. Particularly, men aged <50 with a family history of prostate cancer in a first-or second-degree relative have an approximately five-fold and two-fold increased risk of receiving a prostate cancer diagnosis, respectively.…”
Section: Best Screening Practicesmentioning
confidence: 99%
“…40 Furthermore, the nested case-control study referenced above identified that the risk of developing metastatic disease within 15 years for a man of any age with PSA <1 ng/ml is very low. 39 As such, allowing a longer interval between PSA testing for these men is unlikely to result in an increase in prostate cancer morbidity or mortality and will potentially reduce the risk of over-detection as a result of leadtime bias or natural fluctuations in PSA levels.…”
Section: Best Screening Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a growing body of evidence from nonrandomized but very wellcharacterized-and, in one case, completely uncontaminated-cohorts indicates that the use of PSA at earlier ages, when benign prostatic hyperplasia and related processes are less likely to drive false-positive PSA elevation, could effectively stratify men to early detection, repeat PSA testing, or extended deferral of further testing. Under such a strategy, the majority of men tested once at 45 or 50 yr could defer any further consideration of prostate cancer risk for a decade or more [14,15].…”
mentioning
confidence: 99%
“…For a 55-yr-old man, the question is outcomes at 30 yr and more. While the guideline reflects the latest follow-up reported to date for the ERSPC trial, the evidence is abundantly clear that mortality risk increases sharply with longer follow-up, and that, by extension, the number of lives saved rises and the numbers needed to screen and treat fall accordingly [14][15][16][17]. Randomized trials yield valuable insights, but a new trial randomizing men younger than 50 yr is extremely unlikely at this stage, and avoiding contamination in a control arm in any developed country would be pragmatically impossible.…”
mentioning
confidence: 99%